The cooperative as a reference for the development of the legislative ecosystem of the social economy - Domínguez Cabrera, María del pino (Cooperativismo & Desarrollo, 2025)
The Autonomous Community of the Canary Islands has the legal basis to work in the social economy, and it should certainly not be oblivious to this need. It is within this framework that the social economy in the territory is analyzed, offering solutions to problems of interpretation of the Spanish legal system, which are novel in nature, insofar as they have a positive impact by clarifying its conceptualization, bearing in mind that the state legislative framework has begun the process of modification and, therefore, the changes in this area will affect special regulations in the social economy. This introduces an aspect into the legal debate that opens as a consequence of the reforms, using cooperative principles as a reference for action.